Persuasi Politik melalui Bantuan Sosial: Studi Kasus tentang Persepsi Publik dan Perilaku Memilih pada Pemilihan Umum 2024 - Rohmad Aditiya Utama; Suciati Suciati (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This writing discusses the analysis of the impact of social assistance on public perception and voting behavior in the 2024 General Election. Through interviews with various informants, the research findings reveal diverse views regarding the relationship between social assistance and voting behavior. The findings categorize the main themes into perceptions of social assistance, the influence of social assistance on voting behavior, and factors influencing voter decisions. The research results indicate that the receipt of social assistance does not have a significant direct influence on voter decisions in the general election. Factors such as personal integrity, candidate performance, and their vision and mission play a more determining role in the decision-making process by voters. Although social assistance may be considered a strategy of money politics, its effect on voter behavior is limited. This research highlights the importance of integrity, transparency, and accountability in providing social assistance to ensure that its goals for social welfare are not compromised by political interests. Proposed recommendations include increasing transparency and accountability in the provision of social assistance, political education for the public, strengthening democratic principles in social assistance programs, and encouraging active participation of the community in the democratic process. These findings provide important insights into the dynamics of voter behavior and emphasize that voters have the ability to make independent decisions based on substantial considerations of the quality and potential of candidates.